Peningkatan Literasi Digital Masyarakat Kuin Cerucuk dalam Menghadapi Hoaks di Era Digital: Enhancing Digital Literacy among Kuin Cerucuk Residents to Combat Hoaxes in the Digital Era - Maghfiroh, Sahara; Alhally, Arafat; Muhamad, Said (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
In the rapidly developing digital era, the spread of hoax information has become a serious threat to society, especially in the contexts of social, political, and health issues. The community service program Digital Savvy Citizens Wisely Face Hoaxes